2019
DOI: 10.3390/pharmaceutics11020063
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-Conjugated Polymeric Nanoparticle for Receptor-Mediated Delivery of Doxorubicin in Doxorubicin-Resistant Breast Cancer Cells

Abstract: In this study, a transferrin (Tf)-conjugated polymeric nanoparticle was developed for the targeted delivery of the chemotherapeutic agent doxorubicin (Dox) in order to overcome multi-drug resistance in cancer treatment. Our objective was to improve Dox delivery for producing significant antitumor efficacy in Dox-resistant (R) breast cancer cell lines with minimum toxicity to healthy cells. The results of our experiments revealed that Dox was successfully loaded inside a transferrin (Tf)-conjugated polymeric na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…Compared to unmodified NPs, transferrin-modified NPs have been shown to exhibit higher cellular uptake efficiency and enhanced intracellular delivery of drugs ( Cui et al, 2017 ). Moreover, evidence indicates that transferrin-conjugated polymeric NPs play a significant role in overcoming drug-resistant chemotherapy ( Soe et al, 2019 ).…”
Section: Active Targetingmentioning
confidence: 99%
“…Compared to unmodified NPs, transferrin-modified NPs have been shown to exhibit higher cellular uptake efficiency and enhanced intracellular delivery of drugs ( Cui et al, 2017 ). Moreover, evidence indicates that transferrin-conjugated polymeric NPs play a significant role in overcoming drug-resistant chemotherapy ( Soe et al, 2019 ).…”
Section: Active Targetingmentioning
confidence: 99%
“…Such formed nanoparticles were evaluated in vivo and confirmed pronounced inhibition of tumor growth in mice using the Dalton Lymphoma ascites (DLA) model. Soe et al (2019) demonstrated on the other hand how one can improve the DOX delivery via utilization of the polymeric nanoparticles for the Doxorubicin-Resistant breast cancer cells [ 153 ].…”
Section: Cancer Nanopharmaceuticalsmentioning
confidence: 99%
“…The intracellular accumulation of drugs in a robust tumour environment increases with passive targeting strategy and this is achieved through increased permeability and retention effect. Actively guided NPs have beneficial effects on chemotherapeutic drug delivery mechanisms such as enhancing drug persistence in cancer cells by improving cell attachment, drug accumulation, and increase uptake by cancer cells through receptor‐mediated endocytosis [14]. Metallic NPs are used in photothermal therapy (PTT) and showed excellent results in vivo by thermal ablation of the tumour (Fig.…”
Section: Nanotherapeutics For Cancer Treatmentmentioning
confidence: 99%
“…Doxorubicin (DOX) is one of the most effective chemotherapeutic agents used in the treatment of many cancers, such as breast and ovarian cancer. It can kill cancer cells directly by DNA damage or by elevated ROS and thus inducing apoptosis in the tumour cells [14, 78]. To combat MDR in the treatment of cancer, a current study described the development of transferrin (Tf)‐conjugated polymeric NP for the targeted delivery of DOX.…”
Section: Application Of Hybrid Nps Against Different Type Of Cancersmentioning
confidence: 99%
See 1 more Smart Citation